A Modified Behavior Risk Factor Surveillance System to Assess Diabetes Self-management Behaviors and Diabetes Care in Monterrey Mexico: A Cross-sectional Study - McEwen, Marylyn Morris; Elizondo-Pereo, Rogelio Andrès; Pasvogel, Alice E.; Meester, Irene; Vargas-Villarreal, Javier; González-Salazar, Francisco (Frontiers in Public Health, 2017)
Type 2 diabetes mellitus (T2DM) is one of the leading causes of death from worldwide non-communicable diseases. The prevalence of diabetes in the Mexico (MX)–United States border states exceeds the national rate in both countries. The economic burden of diabetes, due to decreased productivity, disability, and medical costs, is staggering and increases significantly when T2DM-related complications occur. The purpose of this study was to use a modified behavioral risk factor surveillance system (BRFSS) to describe the T2DM self-management behaviors, diabetes care, and health perception of a convenience sample of adults with T2DM in Monterrey, MX. This cross-sectional study design, with convenience sampling, was conducted with a convenience sample (n = 351) of adults in the metropolitan area of Monterrey, MX who self-reported a diagnosis of T2DM. Potential participants were recruited from local supermarkets. Twenty-six diabetes and health-related items were selected from the BRFSS and administered in face-to-face interviews by trained data collectors. Data analysis was conducted using descriptive statistics. The mean age was 47 years, and the mean length of time with T2DM was 12 years. The majority was taking oral medication and 34% required insulin. Daily self-monitoring of feet was performed by 56% of the participants; however, only 8.8% engaged in blood glucose self-monitoring. The mean number of health-care provider visits was 9.09 per year, and glycated hemoglobin level (HbA1c) was assessed 2.6 times per year. Finally, only 40.5% of the participants recalled having a dilated eye exam. We conclude the modified BRFSS survey administered in a face-to-face interview format is an appropriate tool for assessing engagement in T2DM self-management behaviors, diabetes care, and health perception. Extension of the use of this survey in a more rigorous design with a larger scale survey is encouraged.